Diagnostic Precision Of Frozen Section Analysis In Ovarian Tumors: A Comprehensive Study (Journal of Pharmaceutical Negative Results, 2019)
Background: Ovarian tumours form the gamut of neoplastic lesions that display a range of benign to malignant features, which makes diagnosis a hard task for clinicians. Placing the target on the biopsy lesions is the most important for surgical procedures that will be guided by such information.Objectives: The present investigation seeks to evaluate the capability of frozen section analysis to distinguish between the different types of ovarian cancers in the environment of microscopic tumours.Study design: A cross-sectional study.Place and duration of study: Department of pathology Watim medical and dental college, Rawat from 05-March 2018 to 05 Dec 2018.Methods The study was ethically approved and 250 patients diagnosed with ovarian cancer were enrolled. The data collected was structured based on factors such as patient age, tumour dimensions, and morphological features that were judiciously recorded. Paraffin-embedded tissue blocks were serially sectioned in rapid progression. Frozen sections were processed and stained with hematoxylin and eosin for immediate frozen section diagnosis. The tissue was later processed for permanent sections as well.Results: Since the cohort had 2,000-75-year-olds with a mean age of 38 years, tumour size was 2 cm-40 cm with a mean of 12 cm. Also, in 24 cases, the lesions were bilateral. Distribution of the lesions, which were executed only in permanent section analysis, consisted of non-neoplastic lesions, epithelial tumours, sex cord-stromal tumours, germ cell tumours, and metastatic tumours.Conclusion: Within our study, the diagnostic accuracy of the frozen section histopathological method in the differential diagnosis between benign and malignant ovarian tumours is emphasized. Tumour borderline detection capability is one of its strong sides, but it still requires clarification in some cases.